Towards climate-adaptive development of small hydropower projects in Himalaya: a multi-model assessment in Upper Beas Basin - Shirsat, Tejal S.; Kulkarni, Anil V.; Momblanch, Andrea; Randhawa, S.S.; Holman, Ian P. (Elsevier, 2021)
Study Region: Allain catchment, a sub-basin of Beas basin, Western Himalaya Study Focus: This study aims to assess future glacio-hydrological changes in a small basin and their impacts on the operation of two Small Hydropower Projects (SHP) with contrasting hydrological requirements. The Water Evaluation and Planning (WEAP) model is used to integrate cryosphere, hydrology and hydropower production modelling in the 21st century using climate changes projected by the ensembles of five global climate models under RCP 4.5 and 8.5. New Hydrological Insights for the Region: The total streamflow in the future is projected to have widespread uncertainty in the magnitude but shows noticeable changes in the seasonality. Of the two SHPs, the one utilizing high flows with low hydraulic head shows a power generation behaviour similar to streamflow projections. Its annual hydropower production is projected to change by 2 to 21% (RCP4.5) and -5 to 40% (RCP8.5) by the end of the century. The other plant that uses lesser flows but high head maintains its designed power production consistently throughout the century. The study indicates that the design of hydropower plants strongly influences their sensitivity to future climate and thus provides important insights into the climate-adaptive designs and planning of future hydropower projects in Himalaya.
Keywords: WEAP; Climate Change, modelling; Snowmelt; Indus; Glaciers